Community counseling: an opportunity and challenge (Indonesian and American perspective) - Astuti, Budi (Universitas Negeri Yogyakarta, 2020)
The purpose of this article is to explore the opportunity and challenge of implementing community counseling from Indonesian and American perspective. This article used a literature study approach. The literature study was conducted by reviewing books, journals, and research results publications from 2000 to 2017 and previous publications related to community counseling. Data analysis techniques in this study are quantitative data analysis techniques and qualitative data analysis techniques. This article concluded that the possible opportunity that can be applied to meet the challenge faced in achieving the optimization of the implementation of community counseling in Indonesia and America. Community counseling in the Indonesian perspective has the opportunity to be applied in formal and non-formal setting, but the challenge needs to be the provision of professional human resource and system support. Community counseling in the American perspective has the opportunity for rapid development in non-formal setting, but the challenge lies in the complexity of cultural issue and group identity.